Supporting Rural Women During Pregnancy: Baby BEEP Nurses. Issue 1 (January 2017) - Evans, Emily C.; Bullock, Linda F.C.
Abstract: Purpose: The aim of this study was to characterize nursing care provided by the research nurses from the Baby Behavioral Educational Enhancement of Pregnancy (Baby BEEP) study as they delivered a telephone social support intervention to low-income, pregnant women in the Midwestern United States. Study Design and Methods: This was a descriptive qualitative study that used Peplau's Theory of Interpersonal Relations to frame and interpret the analysis. Results: Research nurses from the Baby BEEP study found a novel way to reach a vulnerable population through weekly telephone interactions. Acting in several of Peplau's nursing roles, the care they provided led to a remarkable retention rate and therapeutic nurse–patient relationships. The Baby BEEP study demonstrated the provision of a well-received psychosocial support intervention that can be used to help underserved women throughout pregnancy. Clinical Implications: Telenursing care provided to low-income, rural women was well received and reflected the principles in Peplau's Theory of Interpersonal Relations. Nurses may use this type of nursing care to support women who are difficult to reach and typically experience low levels of support. This article describes the nursing care provided by the Baby BEEP nurses and provides a model for future, novel approaches to social support in a vulnerable and difficult-to-reach population. Abstract : This study shows how nurses using tele-nursing can provide meaningful nursing care and develop trusting relationships with low-income pregnant women living in rural settings.